A literature analysis of the mechanism, application, and future potentials of PV solar cells - Zhao, Wentian (Transactions on Environment, Energy and Earth Sciences, 2026)
With the exacerbated environmental issues and energy shortage, renewable energy is progressively accentuated for sustainable development. Solar energy is casted a striking light for electricity supply in human use. Accordingly, PV solar cells, devices storing and supplying electricity, are applied more extensively in multiple areas including residential usage, production, and facilities. Due to their renewable nature and multifaced applicability, humans are committed to invoke their potentials to more ameliorate reliance on fossil fuels. Through literature review, this article analyzes the essential operational mechanism of solar cells, compares attributes of different types of commonly used solar cells, including silicon-based types, thin-film types, organic types, among others, and discusses their application in various industries regarding future potential trend. Finding that P-N junction is indispensable for energy conversion within solar cells, traditional silicon-based solar cells are evolving through incorporating with organic materials, obviating inefficiency and vulnerability of solely used organic solar cells. Moreover, through cooperating with other energy types, PV solar cells supplement electricity necessary to diverse industries, considerably augmenting energy efficiency. However, future commitments requiring interdisciplinary human capitals and technologies are equally significant to increasing public awareness to further optimize solar cells usage. This article is instrumental in deepening comprehension of basic function of solar cells with their distinctive traits, serving as reference contributing to proper practices in future implementation sustainably.
Keywords: PV solar cells; mechanism; application; prospection.